2012
DOI: 10.1098/rsob.120096
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ASIC channels by a stomatin/STOML3 complex located in a mobile vesicle pool in sensory neurons

Abstract: A complex of stomatin-family proteins and acid-sensing (proton-gated) ion channel (ASIC) family members participate in sensory transduction in invertebrates and vertebrates. Here, we have examined the role of the stomatin-family protein stomatin-like protein-3 (STOML3) in this process. We demonstrate that STOML3 interacts with stomatin and ASIC subunits and that this occurs in a highly mobile vesicle pool in dorsal root ganglia (DRG) neurons and Chinese hamster ovary cells. We identify a hydrophobic region in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 61 publications
(110 reference statements)
4
51
0
Order By: Relevance
“…Moreover, deletion of Atat1 was remarkably selective in that it impacted only on cutaneous mechanosensation and had no effect on thermal responses, or on electrical or other functional properties of sensory neurons such as their sensitivity to capsaicin and pH. We have previously reported that STOML3, another critical mediator of mechanotransduction, associates with microtubules in a specialized vesicle where it interacts with acid-sensing (proton-gated) ion channel (ASIC) subunits (Lapatsina et al, 2012). Uncoupling of vesicles from microtubules leads to incorporation of STOML3 into the plasma membrane and increased acid-gated currents.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, deletion of Atat1 was remarkably selective in that it impacted only on cutaneous mechanosensation and had no effect on thermal responses, or on electrical or other functional properties of sensory neurons such as their sensitivity to capsaicin and pH. We have previously reported that STOML3, another critical mediator of mechanotransduction, associates with microtubules in a specialized vesicle where it interacts with acid-sensing (proton-gated) ion channel (ASIC) subunits (Lapatsina et al, 2012). Uncoupling of vesicles from microtubules leads to incorporation of STOML3 into the plasma membrane and increased acid-gated currents.…”
Section: Discussionmentioning
confidence: 99%
“…Since STOML3 is the only protein known to participate directly in fast mechanotransduction it was of interest to examine how this membrane protein is trafficked within sensory neurons. We found that STOML3 is localized to a highly mobile and molecularly distinct transport vesicle within cultured sensory neuron axons (Lapatsina et al, 2012b).…”
Section: Cell Biology Of Long Lasting Sensitization Induced By Ngfmentioning
confidence: 97%
“…The STOML3 vesicle is obviously enriched in proteins are destined to function in transduction at the peripheral endings of sensory neurons and so we have proposed to name these vesicles "transducosomes". Indeed uncoupling of the "transducosome" from microtubules leads to rapid incorporation into the plasma membrane with an accompanying increase in acid-gated currents (Lapatsina et al, 2012b). Ex vivo recordings from sensory afferents innervating the skin have demonstrated that transduction of mechanical stimuli at the peripheral endings of sensory neurons is very stable for many hours in the absence of a connection to the cell body.…”
Section: Cell Biology Of Long Lasting Sensitization Induced By Ngfmentioning
confidence: 99%
See 2 more Smart Citations